Lucas Davenport : Gathering Prey - Book 25 - Sandford, John, 1944 February 23-; Ferrone, Richard (New York, NY : Penguin Audio, 2015)
"They call them Travelers. They move from city to city, panhandling, committing no crimes. They just like to stay on the move. And now somebody is killing them. Lucas Davenport's adopted daughter Letty is home from college when she gets a phone call from a woman Traveler she'd befriended in San Francisco. The woman thinks somebody's killing her friends, she's afraid she knows who it is, and now her male companion has gone missing. She's hiding out in North Dakota, and she doesn't know what to do. Letty tells Lucas she's going to get her, and, though he suspects Letty's getting played, he volunteers to go with her" --
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Private investigators -- Fiction; Drifters -- Fiction -- Crimes against; Murder -- Fiction -- Investigation; Serial murder investigation -- Fiction; Suspense fiction; Audiobooks